Simulation of W dust transport in the KSTAR tokamak, comparison with fast camera data. (August 2017) - Autricque, A.; Hong, S.H.; Fedorczak, N.; Son, S.H.; Lee, H.Y.; Song, I.; Choe, W.; Grisolia, C.
Highlights: Image processing routines for dust tracking on CCD camera videos are presented. A dust transport simulation tool is presented. Application of the two previous points on an example is shown (2015 KSTAR dust injection experiment). Abstract: In this paper, dust transport in tokamak plasmas is studied through both experimental and modeling aspects. Image processing routines allowing dust tracking on CCD camera videos are presented. The DUMPRO (DUst Movie PROcessing) code features a dust detection method and a trajectory reconstruction algorithm. In addition, a dust transport code named DUMBO (DUst Migration in a plasma BOundary) is briefly described. It has been developed at CEA in order to simulate dust grains transport in tokamaks and to evaluate the contribution of dust to the impurity inventory of the plasma. Like other dust transport codes, DUMBO integrates the Orbital Motion Limited (OML) approach for dust/plasma interactions modeling. OML gives direct expressions for plasma ions and electrons currents, forces and heat fluxes on a dust grain. The equation of motion is solved, giving access to the dust trajectory. An attempt of model validation is made through comparison of simulated and measured trajectories on the 2015 KSTAR dust injection experiment, where W dust grains were successfully injected in the plasma using a gun-type injector. The trajectories of the injected particles, estimated using the DUMPRO routines applied on videos from the fast CCD camera in KSTAR, show two distinct general dust behaviors, due to different dust sizes. Simulations were made with DUMBO to match the measurements. Plasma parameters were estimated using different diagnostics during the dust injection experiment plasma discharge. The experimental trajectories show longer lifetimes than the simulated ones. This can be due to the substitution of a boiling/sublimation point to the usual vaporization/sublimation cooling, OML limitations (eventual potential barriers in the vicinity of a dust grain are neglected) and/or to the lack of a vapor shielding model in DUMBO.